Adsorption of nitrate as a groundwater pollutant by soil particles - Nakayama, Chieko; Tanaka, Yoshinori (Journal of Nepal Geological Society, 2006)
This study discusses nitrogen adsorption in several soil samples of the Kanto loam collected from two locations in the Kanto plain. Their chemical properties were assessed on each of the soil samples as well as on pure allophane clay by instrumental analysis using batch and soil column tests. Nitrogen-nitrate adsorption by soil samples was determined by a 10-hour batch test using a nitric acid solution of 0.14 mmol. A saturation column test was conducted to obtain a breakthrough curve and calculate the coefficients of dispersion and retardation. The extent of nitrate adsorption in soil samples was confirmed by percolation with 0.14 mmol nitric acid through columns packed with the soil sample and silicate sand. In the batch test, it was found that the amount of nitrate adsorption was greater in allophane-rich volcanic ash soils with the amount of nitrate adsorption increasing under conditions of low pH. The breakthrough curve determined by the column test showed that the coefficient of retardation increased in allophane-rich soils. Adsorption of nitrates by Kanto loam soils was thus found to be dependent upon the content of allophane and amorphous material in the soil. Since the positive charge of allophane has the potential to reduce the nitrate content in groundwater, it can be effectively applied to reduce nitrate contamination in groundwater.